Distribution of Edibles Wild Taro (Aroid Plant) on The Different Altitude (Shoutern Slope of Wonogiri and Pacitan) - Puji Wicaksono, Karuniawan; Murniyanto, Eko; Nakagoshi, Nobukazu (AGRIVITA, Journal of Agricultural Science, 2010)
On the dry region of Wonogiri Regency and Pacitan Regency, in the Central Java and East Java Provinces border of Indonesia, there is a potential group of plant which is still disguise from the researchers attention. These wild edible tuberous plant, were actually have potential source of carbohydrate as an alternative to rice or corn inside the forest system or agro-forestry system. Their minimum maintenance, adaptability to drought and shading make them a potential plant as the staple food for the local people residing inside or in the forests buffer zone. Wild taro (Aracaceae family) existence in the forest system or agro-forestry might increase the economic sustainability of forest. Using a Randomized block design method on the 5 plots sample located on the Northern slope of Wonogiri dry-land, the density and distribution type of wild taro and taro-like plants were surveyed. There were six genus of wild tuberous plant with 12 identified species and several endemic species identified. Xantosoma sp has the highest population, and generally the aroid plants have clumped distribution. Current situation of economical importance of other commodity and relationship with human agricultural activities may vary the distribution of Taro.Keywords: Edible wild taro, distribution, altitude